2004
DOI: 10.1007/s10858-004-4056-7
|View full text |Cite
|
Sign up to set email alerts
|

Homonuclear chemical shift correlation in rotating solids via RN?n symmetry-based adiabatic RF pulse schemes

Abstract: The efficacy of RN(nu) (n) symmetry-based adiabatic Zero-Quantum (ZQ) dipolar recoupling schemes for obtaining chemical shift correlation data at moderate magic angle spinning frequencies has been evaluated. RN(nu) (n) sequences generally employ basic inversion elements that correspond to a net 180 degrees rotation about the rotating frame x-axis. It is shown here via numerical simulations and experimental measurements that it is also possible to achieve efficient ZQ dipolar recoupling via RN(nu) (n) schemes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…15 N‐ 15 N chemical‐shift correlation experiments have enabled us to show the presence of canonical GC base pairs in this RNA 4. In addition, analysis of the observed 13 C chemical shifts for the sugar carbon atoms suggested that (CUG) 97 adopts an A‐form helix conformation with a C3′‐ endo sugar pucker and an anti conformation of the glycosidic torsion angle χ 5. Herein, we have explored the possibility of obtaining structural information directly by exploiting the dependence of inter‐ and intranucleotide 1 H– 1 H distances on RNA conformation.…”
Section: Distance Ranges For H6/h8 To Sugar Protons As Extracted Frommentioning
confidence: 89%
See 1 more Smart Citation
“…15 N‐ 15 N chemical‐shift correlation experiments have enabled us to show the presence of canonical GC base pairs in this RNA 4. In addition, analysis of the observed 13 C chemical shifts for the sugar carbon atoms suggested that (CUG) 97 adopts an A‐form helix conformation with a C3′‐ endo sugar pucker and an anti conformation of the glycosidic torsion angle χ 5. Herein, we have explored the possibility of obtaining structural information directly by exploiting the dependence of inter‐ and intranucleotide 1 H– 1 H distances on RNA conformation.…”
Section: Distance Ranges For H6/h8 To Sugar Protons As Extracted Frommentioning
confidence: 89%
“…13 C homonuclear isotropic chemical‐shift correlation spectra of a uniformly { 15 N, 13 C}‐labeled sample of (CUG) 97 obtained with different short proton spin diffusion mixing times are shown in Figure 2. The resonance assignments indicated are based on our recent studies 5. 14 The expected crosspeaks arising from direct or relayed magnetization transfers originating from sugar proton–sugar proton dipolar interactions and corresponding to intranucleotide proton–proton distances of <3.0 Å are seen.…”
Section: Distance Ranges For H6/h8 To Sugar Protons As Extracted Frommentioning
confidence: 94%
“…Spin system-specific assignment of ribose resonances by conventional 13 C-detected ssNMR at MAS frequencies < 20 kHz can be achieved using a multitude of correlation schemes provided a satisfactory spectral linewidth is obtained. In the pioneering study by the Görlach group, mostly intra-ribose and partially ribose-base correlations were obtained using symmetry-based adiabatic ZQ recoupling experiments (Riedel et al, 2004). However, due to the low chemical shift resolution arising from limitations in sample preparation, spin system-specific assignment was not possible despite only three different nucleotides being present in the (CUG) 97 RNA.…”
Section: Ribose Assignmentmentioning
confidence: 99%
“…In most cases, nucleotide-type selective labeling is necessary to overcome severe resonance overlap. Ribose carbons could be correlated through homonuclear 13 C, 13 C correlation experiments like symmetry-based recoupling [37], PDSD [38], DARR [39] or novel PAR [40] experiments; intranucleotide ribose-base connections could be obtained through PDSD correlation as well utilizing longer mixing time (Figure 1B). In 13 C, 13 C PDSD experiment after initial cross-polarization (CP) from 1 H to 13 C, 13 C chemical shifts are evolved during t 1 .…”
Section: Rna Preparation For Ssnmr Studiesmentioning
confidence: 99%